"House Calls" by Mobile Integrated Health Paramedics for Patients with Heart Failure: A Feasibility Study. (2nd November 2022) - Feldman, Bruce A.; Rivera, Orlando E.; Greb, Christopher J.; Jacoby, Jeanne L.; Nesfeder, Jennifer; Secheresiu, Paul; Shah, Mahek; Sundlof, Deborah W.
Abstract : Background: Early readmissions following hospital discharge for heart failure (HF) remain a major concern. Among the various strategies designed to reduce readmissions, home evaluations have been observed to have a favorable impact. We assessed the feasibility of integrating community paramedics into the outpatient management of HF patients. Methods: Selected paramedics completed an educational HF curriculum. These Mobile Integrated Health Paramedics (MIHP) performed scheduled home visits 2- and 15-days post-discharge for patients with Stage C HF (Phase I) and patients with Stage D HF (Phase II). Facilitated by a Call Center, a process was created for performing urgent MIHP house calls within 60 minutes of a medical provider's request. A HF specialist, with an on-call emergency department command physician, could order an intravenous diuretic during home visits. During each phase of the study the incidence of 30-day HF readmissions, 30-day all-cause readmissions, emergency room evaluations, unplanned office encounters, as well as any adverse events were prospectively documented. Results: Collaborative relationships between our hospital network and local EMS organizations were created. There were 82 MIHP home visits. Eight patients received urgent home evaluations within 60-minutes post-request, one requiring transport to an ED. The incidence of all-cause 30-day readmissions in 20 Stage C and 20 Stage D patients was 15% and 40%, respectively. There were no adverse events attributable to the MIHP house calls. Conclusions: It is feasible to integrate MIHPs into the outpatient management of HF. Signals of effectiveness for reducing early readmissions were observed. Obstacles to creating an effective paramedic "House Calls" program were identified. A randomized trial is required to assess the value of this care process and its impact on early readmissions in patients with Stage C and Stage D HF.